SARI BUAH BIT (BETA VULGARIS) DAN SKOR PLAK ALTERNATIF HERBAL DALAM PERAWATAN KESEHATAN GIGI - Lies Elina; Desi Andriyani; Yenny Lisbeth Siahaan (Poltekkes Kemenkes Medan, 2025)
Dental plaque has a thin, colorless layer that cannot be seen clearly with the naked eye. Some of the ingredients commonly used as disclosing solutions are chemical ones, namelyfucshin, iodinesolution and mercurochrome, but theuseof these ingredients can be detrimental because they can color the oral cavity for hours and have an unpleasant taste. The aim of this research was to determine the plaque score after applying disclosing beet juice to class VII students at UPT SMPN 03 Negeri Agung Way Kanan. The research method and research design used descriptive research methods. In this research, what is described is a description of applying beetroot as a disclosing solution to plaque. The results of the plaque score data using beetroot juice are known. The research results in this study contained a very good score of 0 respondents (0%) a good score of 13 respondents (22.8%) a moderate score of 28 respondents (59.9%) a bad score of 16 respondents (28.1%). The conclusion of this study is that the plaque score results show a median value of 2.8 with the highest plaque score being 28 respondents (49.1%) with amedium plaque score. Beetroot juice can be used as a natural ingredient for plaque examination. The suggestionis that the Tanjungkarang Health Polytechnic Dental Health Department can use beets as an alternative for plaque examination by taking beet juice to be used in plaque examination. It is hoped that this research canserve as input for conducting further research to develop research using fruit or other natural dyes.